Molecular conformation and organic photochemistry : Time-resolved photoionization studies - Brogaard, Rasmus Y. (Springer Theses, Recognizing Outstanding Ph.D. Research, 2012)
Rasmus Brogaard's thesis digs into the fundamental issue of how the shape of a molecules relates to its photochemical reactivity. This relation is drastically different from that of ground-state chemistry, since lifetimes of excited states are often comparable to or even shorter than the time scales of conformational changes. Combining theoretical and experimental efforts in femto-second time-resolved photoionization Rasmus Brogaard finds that a requirement for an efficient photochemical reaction is the prearrangement of the constituents in a reactive conformation. Furthermore, he is able to show that by exploiting a strong ionic interaction between two chromophores, a coherent molecular motion can be induced and probed in real-time. This way of using bichromophoric interactions provides a promising strategy for future research on conformational dynamics.